Pathophysiology And Management Of Inhalation Trauma In Burn Patients: Literature Review - Agus Roy Rusly Hariantana Hamid; I Gusti Putu Hendra Sanjaya; Gede Wara Samsarga; Ni Made Ratih Purnama Dewi (Jurnal Plastik Rekonstruksi, 2020)
Introduction: Inhalational trauma is a significant cause of morbidity and mortality rates in burn patients. The high mortality rate for a burn with inhalation trauma requires a good understanding of the pathophysiology to provide comprehensive treatment.Method: Electronic literature searching of the MEDLINE (PubMed), Cochrane, and Google Scholar databases were conducted. Studies regarding inhalation trauma pathophysiology and its management that were eligible and available were chosen and used in this paper.Result: Inhalational trauma pathophysiology can be divided into three, namely damage to the upper respiratory tract, lower respiratory tract, and systemic toxicity. Management can be divided based on post-exposure early management (0-72 hours) and advanced management (3-21 days).Conclusion: At present, the management of inhalation trauma is still moderately supportive. Further research based on inhalation trauma pathophysiology is still needed for effective management so that later it can reduce the morbidity and mortality rates.